Christoph Ochs. Matthaeus Adversus Christianos. The Use of the Gospel of Matthew in Jewish Polemics Against the Divinity of Jesus - Lasker, Daniel J. (Studies in Christian-Jewish Relations, 2014)
No abstract is available.